Dr JA Gray (1858–1929)–Surgeon to HH The Amir of Afghanistan. (February 2023) - Gray, Simon
Dr Gray was an assistant medical officer at the Islington Workhouse when he was offered the dangerous but well-paid post as surgeon to the Amir of Afghanistan in August 1888. He arrived in Afghanistan in March 1889 and continued in the post until June 1893. He described his experiences in his book, My Residence at the Court of the Amir.